Alkaline air: changing perspectives on nitrogen and air pollution in an ammonia-rich world. (30th October 2020) - Sutton, Mark A.; van Dijk, Netty; Levy, Peter E.; Jones, Matthew R.; Leith, Ian D.; Sheppard, Lucy J.; Leeson, Sarah; Sim Tang, Y.; Stephens, Amy; Braban, Christine F.; Dragosits, Ulrike; Howard, Clare M.; et al.
Abstract : Ammonia and ammonium have received less attention than other forms of air pollution, with limited progress in controlling emissions at UK, European and global scales. By contrast, these compounds have been of significant past interest to science and society, the recollection of which can inform future strategies. Sal ammoniac ( nūshādir, nao sha ) is found to have been extremely valuable in long-distance trade ( ca AD 600–1150) from Egypt and China, where 6–8 kg N could purchase a human life, while air pollution associated with nūshādir collection was attributed to this nitrogen form. Ammonia was one of the keys to alchemy—seen as an early experimental mesocosm to understand the world—and later became of interest as 'alkaline air' within the eighteenth century development of pneumatic chemistry. The same economic, chemical and environmental properties are found to make ammonia and ammonium of huge relevance today. Successful control of acidifying SO2 and NO x emissions leaves atmospheric NH3 in excess in many areas, contributing to particulate matter (PM2.5 ) formation, while leading to a new significance of alkaline air, with adverse impacts on natural ecosystems. Investigations of epiphytic lichens and bog ecosystems show how the alkalinity effect of NH3 may explain its having three to five times the adverse effect of ammonium and nitrate, respectively. It is concluded that future air pollution policy should no longer neglect ammonia. Progress is likely to be mobilized by emphasizing the lost economic value of global N emissions (200 billion yr −1 ), as part of developing the circular economy for sustainable nitrogen management. This article is part of a discussion meeting issue 'Air quality, past present and future'.